Recognition of Brazilian popular traditions and embodied cognitive properties in the sound structure of three piano pieces by Osvaldo Lacerda (Orfeu, 2025)
The involvement with bibliographical and audiovisual sources and bodily experiences in the act of playing a musical instrument generates reflections that promote a deeper aesthetic-perceptive experience between composition, interpretation and reception. In the present process of piano study, this bodily and cognitive involvement with the characteristics of each style expressed in the pieces worked on occurs through the connection between knowledge, sensations and sound articulations socially shared in the processes of musical performance. This article presents theoretical approaches to the practice of a Brazilian repertoire for solo piano, based on phenomenological and embodied cognition perspectives in the study of pianistic action, respectively according to Araújo (2020), Milani (2016), among other authors who bring to light the integration of sensorimotor and sociocultural elements in musical performance, with corporeal, gestural and perceptive approaches. The objective is to conduct an interpretative study of three pieces by composer Osvaldo Lacerda through associations between characteristics of popular traditions that give them their title, their sound structure and related cognitive properties, in turn, learned from the area of ​​musical cognition with contributions from enactivism. The procedures carried out are based on interdisciplinary exploratory research around categories and notions applicable to artistic practice, which is constructed according to articulated methodologies and references.